Analisa Pengaruh Faktor Keuangan Dan Non Keuangan Terhadap Audit Going Concern Dan Audit Report Lag (Studiempiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Eric Eric; Keumala Hayati; Bertha Erica; Vista Listyanita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine and analyze the influence of financial and non-financial factors on going concern audits and audit report lag (an empirical study of manufacturing companies listed on the Indonesian stock exchange. The research approach used is a quantitative approach. The sampling method was purposive sampling, a sample of 68 manufacturing companies listed on the Indonesian stock exchange multiplied by 3 years in the research period Results of research using linear logistic regression Demonstrate return on assets, current ratio, debt asset ratio, total asset turnover, company size, KAP reputation and covid-19 simultaneously Impact significantly to the going concern audit opinion.The results of the study show Return on assets, current ratio, total asset turnover, company size, KAP reputation and Covid-19 have no effect on going concern audit opinion while the debt asset ratio has an effect on going concern audit opinion. current ratio, total asset turnover has an effect on audit reports while Return on assets, company size, KAP reputation and Covid-19 have no effect. The results of logistic regression and multiple linear regression tests for the variables return on assets, current ratio, debt asset ratio, total asset turnover, company size, KAP reputation and Covid-19 simultaneously have a significant impact on going concern audit opinion and audit report lag. Keywords: Return On Assets, Current Ratio, Debt Asset Ratio, Total Asset Turnover, Company Size, KAP Reputation, Covid-19, Going Concern Audit Opinion And Audit Report Lag.